Precision assembly of complex cellular microenvironments using holographic optical tweezers - Kirkham, Glen R.; Britchford, Emily; Upton, Thomas; Ware, James; Gibson, Graham; Devaud, Yannick; Ehrbar, Martin; Padgett, Miles; Allen, Stephanie; Buttery, Lee D.K.; Shakesheff, Kevin M. (Nature Publishing Group, 2015)
The accurate study of cellular microenvironments is limited by the lack of technologies that can manipulate cells in 3D at a sufficiently small length scale. The ability to build and manipulate multicellular microscopic structures will facilitate a more detailed understanding of cellular function in fields such as developmental and stem cell biology. We present a holographic optical tweezers based technology to accurately generate bespoke cellular micro-architectures. Using embryonic stem cells, 3D structures of varying geometries were created and stabilized using hydrogels and cell-cell adhesion methods. Control of chemical microenvironments was achieved by the temporal release of specific factors from polymer microparticles positioned within these constructs. Complex co-culture micro-environmental analogues were also generated to reproduce structures found within adult stem cell niches. The application of holographic optical tweezers-based micromanipulation will enable novel insights into biological microenvironments by allowing researchers to form complex architectures with sub-micron precision of cells, matrices and molecules.